Proceedings of the 8th ACM Conference on Web Science 2016
DOI: 10.1145/2908131.2908151
|View full text |Cite
|
Sign up to set email alerts
|

Because science is awesome

Abstract: In this paper, we examine the motivations for participation in Eye-Wire, a Web-based gamified citizen science platform. Our study is based on a large-scale survey to which we conducted a qualitative analysis of survey responses in order to understand what drives individuals to participate. Based on our analysis, we derive 18 motivations related to participation, and group them into 4 motivational themes related to engagement. We contextualize our findings against the broader literature on online communities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 38 publications
3
17
0
2
Order By: Relevance
“…The findings of this study also point to the value of sharing and openness for sustaining a healthy community, a notion consistent with the importance of a sense of inclusion for both intrinsically and extrinsically motivating and encouraging participants to continue contributing to GZ (Greenhill et al 2016). In relation to Foldit, our findings resonate with the study of three gamified citizen science projects conducted by Tinati et al (2016), who found that extrinsic motivations such as having fun and the ability to compete with others, along with intrinsic motivations such as helping to improve scientific knowledge, were important.…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this study also point to the value of sharing and openness for sustaining a healthy community, a notion consistent with the importance of a sense of inclusion for both intrinsically and extrinsically motivating and encouraging participants to continue contributing to GZ (Greenhill et al 2016). In relation to Foldit, our findings resonate with the study of three gamified citizen science projects conducted by Tinati et al (2016), who found that extrinsic motivations such as having fun and the ability to compete with others, along with intrinsic motivations such as helping to improve scientific knowledge, were important.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, Hamari [43] study shows that badges can impact on social comparison and this subsequently mediates user activity. Other studies show instead how social motivation and a sense of community influence data collection in the context of crowdsourcing [61,65]. It is evident in the review that the specific domains and context sometimes regulate the use of social components as psychological mediators.…”
Section: Engagement/flowmentioning
confidence: 98%
“…Y. Lee et al, 2013;Y. Liu, Alexandrova, Nakajima et al, 2011;Machnik et al, 2015;Martella et al, 2015;Massung et al, 2013;Melenhorst et al, 2015;Nose and Hishiyama, 2013;Packham and Suleman, 2015;Pothineni et al, 2014;Prandi et al, 2016;Preist et al, 2014;Prestopnik and Tang, 2015;Roengsamut et al, 2015;Runge et al, 2015;Saito et al, 2014;Simões and De Amicis, 2016;Snijders et al, 2015;Sørensen et al, 2016;Talasila et al, 2016;Tinati et al, 2016;Vasilescu et al, 2014 37 33.6 Empirical studies with no results on how gamification works in crowdsourcing Bentzien et al, 2013;Brenner et al, 2014;Brito et al, 2015;Cao et al, 2015;Chamberlain, 2014;Cucari et al, 2016;Deng et al, 2016;Dos Santos et al, 2015;Harris, 2014;He et al, 2014;Inaba et al, 2015;Kacorri et al, 2014;Kurita et al, 2016;Lauto and Valentin, 2016;Lessel et al, 2015;Mason et al, 2012;Nagai et al, 2014;Nunzio et al, 2016;Riegler et al, 2015;…”
Section: Descriptive Informationmentioning
confidence: 99%
“…The design of a leaderboard implementation seems, therefore, highly context-dependent. However, Kobayashi et al (2015), T. Y. , and Tinati et al (2016) note that many crowdsourcing approaches follow the '90-9-1' participation rule, implying that only 1% of the users perform almost all of the actions, and consequently, long-term leaderboards that motivate the 1% might therefore also be suitable for some crowdsourcing implementations. In contrast to rankings that generally encourage workers to compare their efforts with others, level systems could be used that motivate by visualizing individual achievements.…”
Section: Recommendations For Designing Gamified Crowdsourcing Systemsmentioning
confidence: 99%
See 1 more Smart Citation